Unintentional non-compliance or sheer ignorance of aircraft safety regulations: a critical analysis of a safety occurrence in Australian general aviation. (6th June 2022) - Yadav, Devinder Kumar; Herbert, James
The highly regulated aviation industry is around 100 years old by now and many large corporations are becoming involved in operations of aircraft. Therefore, aviation regulatory authorities are under pressure to deregulate some aircraft operations activities. However, most safety-sensitive activities, such as who can be carried on board an aircraft in flight, are still regulated under civil aviation regulations. One of the regulations known as 'carriage of passengers on prohibited flights' is directly related to safety of passengers and aircraft. Violation or non-compliance of this regulation may jeopardise the safety of both passengers and the aircraft. This paper illustrates and examines the safety issues by carrying out a case study at a general aviation aircraft operator in Australia, where a non-compliance of this regulation had occurred. The typical flight was carried out as a post-maintenance test flight and members of public were taken on board the flight. The paper also attempts to identify any human factor issue in this case.